Oral delivery of tumor microparticle vaccines activates NOD2 signaling pathway in ileac epithelium rendering potent antitumor T cell immunity - Dong, Wenqian (Oncoimmunology, 2017)
Exploiting gut mucosal immunity to design new antitumor vaccination strategy remains unexplored. Tumor cell-derived microparticles (T-MP) are natural biomaterials that are capable of delivering tumor antigens and innate signals to dendritic cells (DC) for tumor-specific T cell immunity. Here, we show that T-MPs by oral vaccination route effectively access and activate mucosal epithelium, leading to subsequent antitumor T cell responses. Oral vaccination of T-MPs generated potent inhibitory effect against the growth of B16 melanoma and CT26 colon cancer in mice, which required both T cell and DC activation. T-MPs, once entering intestinal lumen, were mainly taken up by ileac intestinal epithelial cells (IEC), where T-MPs activated NOD2 and its downstream MAPK and NF-κB, leading to chemokine releasing, including CCL2, from IECs to attract CD103(+) CD11c(+) DCs. Furthermore, ileac IECs could transcytose T-MPs to the basolateral site, where T-MPs were captured by those DCs for cross-presentation of loaded antigen contents. Elucidating these molecular and cellular mechanisms highlights T-MPs as a novel antitumor oral vaccination strategy with great potential of clinical applications.